Are guidelines for measurement of quality of life contrary to patient‐centred care?. (6th September 2018) - Disher, Timothy; Beaubien, Louis; Campbell‐Yeo, Marsha
Abstract: Aims: A discussion of how quality‐adjusted life years are used to inform resource allocation decisions and highlight how assumptions underpinning the measurement of quality of life are contrary to the principles of patient‐centred care. Background: Cost‐effectiveness analyses (CEAs) can provide influential guidance for health resource allocation, particularly in the context of a budget‐constrained public health insurance plan. Most national economic guideline bodies recommend that quality‐adjusted life year weights for CEA be elicited indirectly (public preferences). This has potentially important implications for healthcare provision and research, as it discounts the ability of a person experiencing an illness to describe how it affects their quality of life. Design: Discussion paper. Data sources: Guidelines for the conduct of health economic evaluations, influential methodological and theoretical texts, and a review of PubMed conducted in April 2017. Implications for Nursing: Nurses are increasingly interested in leveraging methods from health economics to aid in decision‐making and advocacy. In this analysis, we highlight how taken‐for‐granted approaches to the measurement of quality of life may discount the experience of patients and lead to decisions that are contrary to the principles of patient‐centred care. Nurses conducting or reading research using these methods should consider whether the approach used to measure the quality of life are appropriate for the population under consideration. Conclusion: Since patient and public health preferences can differ in both magnitude and direction, guideline bodies should re‐evaluate their partiality for public preferences in the reference case. Abstract : 目标: 讨论质量调整寿命年如何用于告知资源分配决定, 并强调支撑测量生活质量的假设与以患者为中心的护理原则相悖。 背景: 成本效益分析(CEA)可为健康资源分配提供有影响力的指导, 特别是在预算受限的公共健康保险计划的背景下。多数国家经济指导机构认为, 质量调整寿命年间接引出了成本效益分析(公众偏好)。由于低估了患者描述疾病如何影响其生活质量的能力, 这对医疗保健的提供和研究有着潜在的重要影响。 设计: 讨论文件。 数据来源: 健康经济评估行为指南、有影响力的方法和理论文本和2017年4月进行的PubMed数据库审查。 对护理的意义: 护士们越加热衷于利用卫生经济学的方法进行决策和宣传。本分析中, 我们强调, 习以为常的生活质量测量方法可能会低估患者体验, 并导致做出与以患者为中心的护理原则相悖的决定。使用这些方法进行研究的护士应考虑, 用于衡量生活质量的方法是否适用于研究人群。 结论: 由于患者和公众健康偏好在量级和方向上均存在偏差, 指导机构应在参考案例中重新评估其对公众偏好的偏爱。